Investigation on The Stem Bark of Trema orientalis - Malek S.N, Abd; H.S, Lai,; N, Muhammad; Ali N.A, Mohamad; N, Perry, (Malaysian Journal of Science, 2005)
A chemical investigation was conducted on the ethyl acetate-soluble fraction of the stem bark of Trema orientalis. This led to the isolation of seven methyl ester of fatty acids hexadecanoic, (Z,Z)-9,12-octadecadienoic, (Z)-9-octadecenoic, octadecanoic, eicosanoic, docosanoic and tetracosanoic. Two triterpenoids identified as Î²-sitosterol and 3Î²-acetoxyurs-12-en-28-oic acid were isolated. The methyl ester of fatty acids were identified by GC-MS while the triterpenoid compounds were identified using NMR and infrared spectroscopy and mass spectrometry. The identification of 3Î²-acetoxyurs-12-en-28-oic acid was verified by comparing it to the authentic 3Î²-acetoxyurs-12-en-28-oic acid synthesized from the acetylation of ursolic acid.